The Comparative Analysis of Sexual Violence and Harassment at the piloting Universities of Cyprus and Lithuania - Šidlauskienė, Virginija; Pocevičienė, Rasa (Information & Media, 2021)
The sociocultural contexts of higher education institutions form the background for gender-based violence in professional structures and environment of academia. The article presents the comparative analysis of sexual violence and the reasons for its (non-)disclosure at the universities in Lithuania and Cyprus. The findings of focus group interviews conducted within the framework of the Ending Sexual Harassment and Violence in Third Level Education (ESHTE) project, co-funded by the European Union, have been summarized in the present research. The focus group participants from each partner university involved university teachers, administrative staff, counselors and university students. The research was conducted during a 3-month period between 2017 and 2018. The main aim was to investigate university staffs’ and students’ experiences in the disclosures of the cases of sexual violence and harassment (SVH) in university environment and campus, as well as their awareness of  existing procedures and policies in handling the cases of SVH. Their personal experiences, attitudes and beliefs of SVH, as well as any suggestions they have towards the improvement of disclosures of SVH are discussed in the article.
Keywords: sexual violence and harassment (SVH); academic and administrative staff; students; Cyprus; Lithuania